Prospects for cost-efficient water protection in the Baltic Sea - Hyytiäinen, Kari; Ahlvik, Lassi (Elsevier, 2015)
This study investigates the economic consequences of the nutrient load reductions agreed in the 2013 revision of the Baltic Sea Action Plan. The cost of meeting the targets set for waterborne sources was estimated to be 1980 MEUR annually. The 2013 revision is a step towards cost-efficient water protection: the cost of meeting the earlier targets would have been 328 MEUR (14%) higher, although the revised targets are now more ambitious with respect to phosphorus. We demonstrate that there is potential for efficiency gains by introducing flexibility mechanisms, such as ‘joint implementation’ to trans-boundary water protection. The potential gains can be as high as 280 MEUR (14%). The most flexible interpretation of the basin targets, one allowing Contracting Parties to account for reductions in other sea basins in proportion to their effect in the focal basin, could further reduce the total cost by 200 MEUR (12%).
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; eutrophication; target setting; Baltic sea action plan; nitrogen; phosphorus